Improving 795 nm Single-Frequency Laser’s Frequency Stability by Means of the Bright-State Spectroscopy with Rubidium Vapor Cell - Junye Zhao; Yongbiao Yang; Lulu Zhang; Yang Li; Junmin Wang (Photonics)
The utilization of atomic or molecular spectroscopy for frequency locking of single-frequency laser to improve laser frequency stability plays an important role in the experimental investigation of optically pumped atomic magnetometers, atomic clocks, laser cooling and trapping of atoms, etc. We have experimentally demonstrated a technique for frequency stabilization of a single-frequency laser employing the bright state spectroscopy (BSS) with a rubidium atomic vapor cell. By utilizing the counter-propagating dual-frequency 795 nm laser beams with mutually orthogonal linear polarization and a frequency difference of 6.834 GHz, which is equal to the hyperfine splitting of rubidium-87 ground state 5<semantics>S1/2</semantics>, an absorption-enhanced signal with narrow linewidth at the center of Doppler-broadened transmission spectroscopy is observed when continuous scanning the laser frequency over rubidium-87 D1 transition. This is the so-called BSS. Amplitude of the absorption-enhanced signal in the BSS is much larger compared with the conventional saturation absorption spectroscopy (SAS). The relationship between linewidth and amplitude of the BSS signal and laser beam intensity has been investigated. This high-contrast absorption-enhanced BSS signal has been employed for the laser frequency stabilization. The experimental results show that the frequency stability is <semantics>4.4×10−11</semantics> with an integration time of 40 s, near one order of magnitude better than that for using the SAS.